STUDIES PREFERENCE STUDENT TO ELECTION RESIDENCE BOARDING HOUSE - Kemal Al Kindi Mulya; Natasya Nikita Givsa (Jurnal Penelitian Progresif, 2025)
This study aims to identify and analyze factors influencing student preferences in choosing boarding houses in Grogol and Tomang Villages, Grogol Petamburan District, West Jakarta. This study uses a mixed methods approach , combining quantitative and qualitative descriptive methods to gain a comprehensive understanding of student behavior and preferences. Based on the results of the research conducted, it was found that in the selected sample it was known that student income (pocket money) had a significant negative effect on student preferences in determining boarding houses and stated that if income (pocket money) increased, the tendency for students to choose boarding houses in Tomang Village was higher when compared to Grogol Village. Boarding house rental prices had a significant positive effect on student preferences in choosing boarding houses and stated that if boarding house prices increased, the tendency for students to choose boarding houses in Grogol Village was higher when compared to Tomang Village. The facilities offered by boarding houses had a significant positive effect on student preferences in choosing boarding houses and stated that if the boarding house facilities offered were better, the tendency for students to choose boarding houses in Tomang Village was higher when compared to Grogol Village. There was no significant and negative influence between lifestyle variables and student preferences in choosing boarding houses and stated that the high or low level of lifestyle would not increase student preferences in choosing Tomang or Grogol boarding house areas as boarding houses.Meanwhile, based on the concept of price elasticity of demand, boarding houses can be categorized as an elastic good, meaning that demand for boarding houses is highly sensitive to price changes. Based on the income elasticity of demand, boarding houses are classified as a primary necessity for students. This indicates that despite changes in income, demand for boarding houses remains relatively stable because housing is a basic need during the study period. Meanwhile, based on cross-elasticity, there is a substitution relationship between middle- to upper-class boarding houses and middle- to lower-class boarding houses. This means that if the price of middle- to upper-class boarding houses increases, students will tend to switch to middle- to lower-class boarding houses as an alternative, and vice versa.